Deseminasi Program Community Engagement and Professional Development - Rajab, Hadarah (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2021)
The Community Development and Professional Development Program is a short training but provides not simple experience, participants can focus more on developing academic writing, methodology research and scientific insights in the fields of Psychology, Anthropology, Social Science, Cultural Studies, Ethnography and Australian History, besides learning in more developed countries, certainly more appropriate so that in the following periods it could be developed again. The Religion and Society Research is an extension of the Center for the Study of Contemporary Muslim Society (CSCMS) which was established in 2009 at UWS under the umbrella of the National Center of Excellence for Islamic Studies. As such, it is apparent that Islam and the Muslim community have become the basis of studies that are calculated and attracting interest in the UWS and in many other campuses in Australia. Conflicts, especially radical terrorism is not visible on the surface, so when it is questioned, it becomes something that is not interesting for them to be discussed. It is possible that this also exists but is not popular for all parties to talk about it. It is evident that every resource person who appears if at the end of a radical question about terrorism, then he spontaneously says he does not have control and there is no material to convey, therefore he is wrong when providing information because it is outside of their knowledge. His attitude of professionalism seems to be exemplary on the other hand, that means that not everyone can talk about everything, if it is outside their knowledge and understanding, other than that they do not want to rashly provide information that will result in information only alleged without evidence. Program Community Engagement and Professional Development merupakan training singkat namun memberikan pengalaman yang tidak sederhana, peserta dapat lebih focus pada pengembangan academic writing, methodology research dan wawasan keilmuan di bidang Psychology, Antropology, Social Science, Cultural Studies, Ethnography and Australian History, selain itu belajar di negara lebih maju tentu lebih tepat ssehingga dimasa-masa berikutnya dapa dikembangkan lagi. The Religion and Society Research merupakan perluasan dari Center for the Study of Contemporary Muslim Society (CSCMS) yang didirikan tahun 2009 di UWS di bahwa payung National Center of Exellence for Islamic Studies. Dengan demikian, nampak nyata bahwa Islam dan komunitas masyarakat muslim telah menjadi basis kajian yang diperhitungkan dan menarik minat di UWS dan di banyak kampus-kampus lain di Australia. Konflik, radikal apalagi terorisme terbilang tidak nampak dipermukaan, sehingga ketika hal itu dipertanyakan, maka hal itu menjadi sesuatu yang tidak menarik bagi mereka untuk diperbincangkan. Kemungkinan hal itu juga ada namun tidak menjadi populer untuk semua kalangan untuk membicarakannya. Terbukti setiap narasumber yang tampil jika diakhir pertanyaan tenang radikal terorisme, maka ia pun spontan mengatakan tidak menguasai dan tidak ada bahan untuk disampaikan, oleh karenanya ia justru salah jika memberikan informasi karena diluar pengetahuan mereka. Sikap Profesionalismenya nampak disisi lain patut dicontoh, iu artinya tidak semua orang boleh berbicara tentang semua hal, jika memang diluar keilmuan dan pemahaman mereka, selain itu tidak ingin gegabah memberikan informasi yang akibatnya informasi tersebut hanya dugaan tanpa bukti.